2019
DOI: 10.1096/fj.201901166r
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CFTR‐mediated intestinal chloride secretion as potential therapy for bile acid diarrhea

Abstract: Bile acid diarrhea (BAD) is common with ileal resection, Crohn's disease, and diarrhea‐predominant irritable bowel syndrome. Here, we demonstrate the efficacy of cystic fibrosis transmembrane conductance regulator (CFTR) inhibitor (R)‐benzopyrimido‐pyrrolo‐oxazine‐dione‐27 (BPO‐27) in reducing bile acid‐induced fluid and electrolyte secretion in colon. Short‐circuit current measurements in human T84 colonic epithelial cells and planar colonic enteroid cultures showed a robust secretory response following mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Although somatostatin analogs such as octreotide and/or surgical resection are the standard of care for VIPoma ( 28 ), cinacalcet may offer an alternative option for patients who do not tolerate or respond to these treatments. Other potential indications for cinacalcet include medullary thyroid cancer–associated diarrhea ( 29 ), bile acid diarrhea ( 30 ), and tyrosine kinase inhibitor diarrhea ( 19 ), in which increased CFTR-mediated Cl – secretion is a major cause of diarrhea. Cinacalcet may also be effective in some congenital diarrheas such as gain-of-function mutations in GUCY2C , which is associated with excessive cyclic nucleotide-mediated CFTR activation in enterocytes ( 31 ), as well as microvillus inclusion disease, which may involve impaired intestinal absorption and unbalanced CFTR-mediated Cl – secretion ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although somatostatin analogs such as octreotide and/or surgical resection are the standard of care for VIPoma ( 28 ), cinacalcet may offer an alternative option for patients who do not tolerate or respond to these treatments. Other potential indications for cinacalcet include medullary thyroid cancer–associated diarrhea ( 29 ), bile acid diarrhea ( 30 ), and tyrosine kinase inhibitor diarrhea ( 19 ), in which increased CFTR-mediated Cl – secretion is a major cause of diarrhea. Cinacalcet may also be effective in some congenital diarrheas such as gain-of-function mutations in GUCY2C , which is associated with excessive cyclic nucleotide-mediated CFTR activation in enterocytes ( 31 ), as well as microvillus inclusion disease, which may involve impaired intestinal absorption and unbalanced CFTR-mediated Cl – secretion ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have reported both CFTR and FXR to have potential as therapeutic targets for diarrheal disease. A recently published study has implicated CFTR in CDCA-induced Clsecretion in a rat model of bile acid diarrhoea (BAD), with inhibition of CFTR reducing stool water content (Duan et al 2019). Furthermore, previously published data from our laboratory have shown that FXR activation prevents secretory diarrhoea in in vivo models (Mroz et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acid-induced diarrhea is usually caused by an excess of bile acids in the colon due to bile acid malabsorption ( Yde et al, 2016 ), which is very common in patients with inflammatory diseases, such as ileal resection, Crohn’s disease, and diarrhea-predominant irritable bowel syndrome ( Duan et al, 2019 ). An earlier study indicated that the mechanism of bile acid-induced diarrhea might be associated with an increase in mucosal permeability to ion and water and mucosal damage ( Argenzio and Whipp, 1983 ).…”
Section: Role and Regulation Of Aqp3 Expression In Diarrheamentioning
confidence: 99%